Overcoming immune resistance in advanced esophageal squamous cell carcinoma with recombinant human adenovirus type 5 by impacting the immune microenvironment: a case report - Wang, Zhongting; Hong, Junfeng; Wu, Huiping; Zheng, Yan; Lin, Xinchen; Lin, Ying; Wang, Xuzhou; Fang, Wenzheng (Frontiers in Immunology, 2025)
Advanced esophageal squamous cell carcinoma (ESCC) has a poor prognosis. Chemotherapy combined with immune checkpoint inhibitors is a feasible treatment, but effective treatment modalities need to be explored for its immune resistance. H101, a genetically modified oncolytic adenovirus, represents a promising anti-tumor therapeutic strategy due to its ability to selectively replicate in and lyse cancer cells while sparing normal tissues. H101 has shown clinical efficacy in treating nasopharyngeal carcinoma and hepatocellular carcinoma. However, its therapeutic potential in ESCC remains understudied, with limited reports available. We reported a case of a patient with multiple relapses of advanced ESCC who exhibited a progression-free survival (PFS) of 15.5 months following the administration of first-line chemotherapy in conjunction with immunotherapy. At first recurrence, the patient received H101 injection in metastatic lymph nodes with chemo- and immunotherapy, demonstrating a reduction in the left cervical lymph node from 29.1×12.9 mm to 24.6×10.36 mm at 25 days post-injection, and ultimately achieving a PFS of 30 months. During the second recurrence, after undergoing three cycles of the aforementioned combined treatment regimen, the patient experienced significant alleviation of their disease. Following the H101 injection, we noted that the patient experienced transient fever, lymph nodes at both injection and non-injection sites subsided, pathological complete response was achieved, and PFS was significantly prolonged. We also observed significant increases in the expression of CD3, CD4, CD8, CD20 and IL-1β after two relapsed H101 treatments based on multiplex immunofluorescence analysis. Intralymphatic injection of H101 combined with chemotherapy and immunotherapy may represent a promising clinical strategy for advanced ESCC patients with recurrent lymph node metastasis.